2007
DOI: 10.1063/1.2746818
|View full text |Cite
|
Sign up to set email alerts
|

Development of high-pressure, high-field and multifrequency electron spin resonance system

Abstract: The electron spin resonance (ESR) system which covers the magnetic field region up to 16 T, the quasicontinuous frequency region from 60 to 700 GHz, the temperature region from 1.8 to 4.2 K, and the hydrostatic pressure region up to 1.1 GPa has been developed. This is the first pulsed high-field and multifrequency ESR system with the pressure region over 1 GPa as far as we know. Transmission ESR spectra under hydrostatic pressure can be obtained by combining a piston-cylinder-type pressure cell and the pulsed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…6. We already found that the D-value increases as the pressure is increased for this material [24]. The dotted and solid lines in Fig.…”
Section: +supporting
confidence: 57%
See 1 more Smart Citation
“…6. We already found that the D-value increases as the pressure is increased for this material [24]. The dotted and solid lines in Fig.…”
Section: +supporting
confidence: 57%
“…The cylinder and clamping bolts are all made of non-magnetic CuBe alloy. In order to introduce the electromagnetic wave into the sample space, the upper inner parts made of CuBe alloy were replaced by those made of ZrO 2 which was already known to have relatively good transmittance of electromagnetic wave [24] as shown in Fig. 4.…”
Section: Application To High-pressure Measurementmentioning
confidence: 99%
“…Applications for Ni 2 þ (S ¼1) ions in the Haldane gap systems Y 2 BaNiO 5 and Nd 2 BaNiO 5 have been worked out to illustrate the usefulness of these tools. The proposed tools may also enable better understanding of the spectroscopic properties of Ni 2 þ ions in other crystals as well as facilitate applications of high pressure and/or HMF-EMR measurements [63] in the studies of Haldane gap systems, which are still scarce [64].…”
Section: Discussionmentioning
confidence: 99%
“…To date, a combination of high-field/high-frequency ESR system with a high hydrostatic pressure vessel operating above 1 GPa has been reported by only one group [20]. It is a pulsed high-field, multi-frequency (60-700 GHz) system, that operates up to 17 T and covers the hydrostatic pressure range up to 1.1 GPa.…”
Section: Introductionmentioning
confidence: 98%
“…It features a non-resonant transmission-type pressure vessel, which is equipped with two microwave-transparent sapphire plugs. This pressure vessel is located in the same cryostat compartment as the InSb microwave detector, which limits the operating temperature range to 1.8-4.2 K. Notwithstanding the above technical limitation, the non-resonant high-frequency approach described in [20] offers a remarkable simplification of the overall system design, because the complicated resonant microwave structures can be avoided without sacrificing the spectrometer performance [2,21].…”
Section: Introductionmentioning
confidence: 99%